Стихотворения - Рубальская Лариса Алексеевна (Народная поэзия, 2020)
Экземпляры: Абонемент (15.10.2020) / Инвентарный номер: 50981 / Цена: 227.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Р 82 / ББК: 84(2=411.2)6-5